READINESS OF TECHNOLOGICAL LITERACY TOWARD ONLINE SELLING INTEREST AMONG SME’S IN MALANG CITY - Sidi, Agus Purnomo; Hanif, Rifki (Jurnal Apresiasi Ekonomi, 2023)
This study examines the complex relationship between social media use, digital literacy, and online selling among unemployed persons in Malang City. The study used simple linear regression analysis and a Likert scale questionnaire to examine the complex relationships between social media use, digital literacy, and online entrepreneurship. This study provides a comprehensive understanding of the various dynamics and lays the groundwork for future research and strategic interventions to use digital environments to change economic trajectories and empower entrepreneurs. The link between social media use and entrepreneurship shows the power of internet platforms to change lives. It also shows how digital environments may become lively ecosystems that support entrepreneurship. This study advances digital entrepreneurship and workforce growth. Social media, digital skills, and entrepreneurship help Malang's economy. Targeted interventions to improve digital competency and social media use can unleash entrepreneurial spirit in the city.